Physical features of public records regarding the legal admissibility - (:unkn) unknown (TURKIYE ORTA DOGU AMME IDARESI ENSTITUSU, 2007)
Documents created by authorized persons in institutions compliant with administrative procedures and processes, should, at the same time, possess certain physical features of the category to which they belong. These features should be consistent with each other and should be placed in the appropriate places in the document profile, thus providing the user with clues about when and by which governmental body the document is issued. This study discusses physical characteristics of public records regarding legal admissibility. The study attempts to describe how physical features such as signature, seal, number and heading can be used, while determining the legal admissibility of documents as evidences of administrative transactions. The findings of the study can also be used to establish the authenticity of electronically transmitted messages.
Keywords: documents; legal admissibility; official records; physical features; reliability; diplomatics